BUKU MENDONGENG CERITA RAKYAT GROBOGAN SEBAGAI PENGAYAAN MATERI CERITA RAKYAT DI SMP - Thoyyibah, Hannik (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2017)
Penelitian ini bertujuan untuk menghasilkan buku mendongeng cerita rakyat Grobogan sebagai pengayaan materi cerita rakyat di SMP. Penelitian ini menggunakan metode penelitian research and development (R&D). Hasil penelitian ini terdiri atas tiga bahasan, yaitu kebutuhan guru dan siswa terhadap buku pengayaan, prototipe buku pengayaan, dan hasil uji validasi prototipe buku mendongeng cerita rakyat Grobogan sebagai materi cerita rakyat di SMP. Angket kebutuhan guru dan siswa digunakan untuk menyusun prototipe dari buku mendongeng cerita rakyat Grobogan tersebut. Prototipe buku pengayaan yang dikembangkan dikategorikan menjadi tiga bagian utama, yaitu bagian pendahulu, bagian isi, dan bagian penyudah. Bagian pendahulu berisi prakata, petunjuk penggunaan buku, dan daftar isi. Bagian isi berisi materi mendongeng cerita rakyat Grobogan, dari pengertian mendongeng dan cerita rakyat, manfaat cerita rakyat, tujuan dan manfaat dongeng, latihan pramendongeng, tips mendongeng di depan kelas, teknik mendongeng, petunjuk praktis mendongeng, dan contoh teks yang digunakan untuk mendongeng. Sedangkan bagian penyudah berisi biodata penulis dan daftar pustaka. Berdasarkan penilaian yang dilakukan oleh ahli buku dan materi, buku pengayaan ini dapat menarik minat siswa untk belajar mendongeng cerita rakyat secara mandiri. The aim of this study is to produce a storytelling book about folklore in Grobogan as enrichment material for Junior High School student. This study used research and development (R&D) as the method. The result of this study consists of five discussions; they are students’ requirement towards enrichment book, teachers’ requirement towards enrichment book, prototype of enrichment book, prototype’s judgment of enrichment book, and improvement of the prototype of storytelling book about folklore in Grobogan as the material about folklore for Junior High School student. The questionnaire about students and teachers’ needs is used to compile the prototype of this storytelling book which tells about folklore in Grobogan. The prototype of this enrichment book which has been compiled is categorized into three main parts; they are preface part, discussion part, and closing part. The Preface part consists of foreword, instruction for use, and table of contents. Next is discussion part which involves storytelling material of folklore in Grobogan such as the meaning of storytelling and folklore, the advantage of folklore, the purpose and advantage of fairytale, pre-storytelling activities, storytelling tips in the classroom, storytelling technique, practical instruction in storytelling, and example of text which is used for storytelling. last is the closing part which consists of author bio and bibliography. Based in the judgment from book expert and material expert of enrichment book, this book is considered can captivate student’s interest to study storytelling about folklore independently.